A Case of Pulmonary Hypoplasia and Anasarca Syndrome with Palatoschisis in a Calf Fetus - Yüksel, Burak Fatih; Ercan, Kerem; Karabulut, Burak; İncili, Canan Akdeniz; Kalkan, Cahit (My University, 2019)
Pulmonary hypoplasia and anasarca syndrome is a lethal genetic disorder of cattle characterized by excessive subcutaneous edema, undeveloped lungs and fetal hydrops. In this case report, a calf fetus delivered by the cesarean section from a two-year-old Simental breed heifer was presented. Intense fluid was collected between the subcutaneous tissues of the extracted calf. Pathologically, it was found that the animal had diffuse and severe subcutaneous edema, total palatoschisis in the upper palate, the lungs were smaller than normal, atelectatic and hypoplastic, and the heart was bilaterally dilated. Microscopic examination revealed significant histopathologic findings such as epicardial and endocardial edema in the heart and lungs, endocardial fibrosis, fetal atelectasis in the lungs, and perivascular and interstitial edema. This is the first report in Turkey characterized by anasarca and malformation, suggesting this is a rare case in animals.
Keywords: Genel ve Dahili Tıp; Patoloji; Veterinerlik